Efektivitas Kerja Guest Service Agent Dalam Pelayanan Tamu Di Dusit Thani Resort Maldives - Lusia Vreyda Adveni; Shintia Kuswandi (Politeknik Sahid, 2020)
The development of the tourism industry in the world makes businesses stricter in the face of competition. Starting from the restaurant business, travel agents, airlines, to the construction of hotels and resorts. The hospitality industry (Hospitality Industry) is an industry with a classification that includes a variety of commercial facilities and is equipped with food-beverages and services, room accommodation or both. The industry has various groups of operational activities including resorts, which are one of the accommodations that tourists need as a temporary residence during a tour. Facing increasingly fierce competition, various efforts have been made such as, adding facilities, renovating buildings, and increasing the quality of services effectively. Guest service agent is one part that has an important role in the front office department, which has the duty and responsibility of providing comfort to guests. In addition, guest service agents are also required to always do their best to provide maximum information and services. With the research on the performance of guest service agents at Dusit Thani Resort Maldives will answer a variety of problems that are often faced by guest service agents while serving the guests. In addition, the performance of an effective guest service agent will improve the quality of services available at the resort. In this study the author will explain the qualitative analysis method which contains the meaning of a depiction of data and using words and sentence lines. The data analysis method used is triangulation, the author also places more emphasis on objectivity and honesty which is realized by explaining the research objectives to the informants. There are three discussions in this research, namely how the guest services at Dusit Thani Resort Maldives. Second, how the performance of the guest service agent is applied to the front office department. The latter is to find out the effectiveness of the performance of guest service agents in serving the guests, especially in the front office department at Dusit Thani Resort Maldives.